Uso do território e agricultura no Rio Grande do Norte: materialidades e estruturas - Celso Donizete Locatel (Confins)
The agricultural activities, as well as the spatial circuits of production that are constituted from them, are of great importance for the national economic dynamics and, also, for the economic context of the state of Rio Grande do Norte. In the case of RN the agricultural activities contributed with 3,4 % of the state GDP in 2016, besides occupying more than 30 % of the economically active population. In order to understand the agricultural use of the potiguar territory it is necessary to consider the engineering systems that sustain the territory, as well as the agricultural spatial circuits of production formed based on them. Considering that statement, the purpose of this work is to analyze the use of the territory from the main spatial circuits of agricultural production in the state, taking into account the technical density of that activity and the selectivity in relation to the places. With this work it can be verified that the largest employed technical density in agricultural activities in the RN is present in the tropical spatial circuits of fruits production for the export and of sugarcane. The spatial circuits of production of nutritious goods aiming the domestic market as corn, cassava and beans present a reduced cultivated area and low technical level. It was also observed that the low rainfall, a characteristic of the semiarid climate, is not a decisive factor for the low productivity of the most traditional foods circuits, but the low technical density is.